The future of European communication and transportation research: A research agenda - Cathy Macharis; Karst Geurs (REGION, 2019)
Our mobility system is changing rapidly. We are at the crossroad of major changes in the way we travel and deliver goods. Research agendas are adapting to this changed environment with new challenges and opportunities. This paper presents a research agenda for the future of transportation research structured along eight cluster topics of the Network on European Communication and Transport Activities Research (NECTAR). ~The research agenda firstly highlights the growing complexity and need for multi- and interdisciplinary transportation research. Secondly, sustainability needs to be addressed in transportation research in its full meaning, including relationships between policy-making investigations and environmental and equity effects. Thirdly, ICTs and digitalisation, the development of (shared) autonomous vehicles and shared mobility will have profound impacts on economies and spatial interactions all-around the world, and availability of high resolution spatial and transportation data. Digitalisation generates many new research opportunities but also give rise to new concerns about privacy, safety, equity and public health.
Keywords: 330